Temperature‐Dependence of the Clear‐Sky Feedback in Radiative‐Convective Equilibrium. Issue 22 (16th November 2021) - Kluft, Lukas; Dacie, Sally; Brath, Manfred; Buehler, Stefan A.; Stevens, Bjorn
Abstract: We quantify the temperature‐dependence of the clear‐sky climate sensitivity in a one‐dimensional radiative‐convective equilibrium model. The atmosphere is adjusted to fixed surface temperatures between 280 and 330 K while preserving other boundary conditions in particular the relative humidity and the CO2 concentration. We show that an out‐of‐bounds usage of the radiation scheme rapid radiative transfer model for GCMs (RRTMG) can lead to an erroneous decrease of the feedback parameter and an associated "bump" in climate sensitivity as found in other modeling studies. Using a line‐by‐line radiative transfer model, we find no evidence for a strengthening of the longwave radiative feedback for surface temperatures between 305 and 320 K. However, the line‐by‐line simulations also show a slight decrease in climate sensitivity when surface temperatures exceed 310 K. This decrease is caused by water‐vapor masking the radiative forcing at the flanks of the CO2 absorption band, which reduces the total radiative forcing by about 18%. Plain Language Summary: The climate feedback parameter describes how the net radiative balance at the top of the atmosphere changes with surface temperature. The magnitude of the feedback parameter here depends on the current state of the climate system. For example, a warmer climate state is accompanied by a moister atmosphere which limits the climate feedback and hence increase climate sensitivity—which is the surface warming due to a doubling of CO2 . Other modeling studies have shown that the climate sensitivity will first increase in a warmer reference climate, but decrease again when surface temperatures exceed 310 K. In this study, we are using a reference radiative transfer model to show how the misuse of a simplified radiation scheme can lead to this spurious signal in the estimation of the climate feedback parameter. In addition, we explain how changes in the H2 O and CO2 concentrations influence the spectral distribution of both the feedback parameter and the radiative forcing. Key Points: The (negative) clear‐sky radiative feedback monotonically increases for surface temperatures between 280 and 330 K Masking effects by water‐vapor at the flanks of the CO2 band weaken the radiative forcing at high column water vapor At present‐day CO2 concentrations Earth's climate is stable for surface temperatures up to at least 330 K